Makna Ceramah Ust Hanan Attaki: “Celah Syaitan Masuk Ke Dalam Hati Manusia” - Raden Fietra Universalia Adikusumah; Adela Futri Fiziani (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
This research reviews the meaning of Ust Hanan Attaki's lecture entitled "The Gap of Shaitan Entering the Human Heart" through a Youtube page uploaded by Ust Hanan Attaki's personal Youtube account. This study aims to find out the gap in shaitan entering the human heart. As is already known that shaitan will tempt humans until the end of time. Shaitan will do everything possible to tempt people and invite them to go to hell with them. It began when God created the first man who was the Prophet Adam AS. Allah Almighty commanded the angels and shaitans to kowtow to men. All angels were always obedient to God's commands and prostrated themselves to the first man, the Prophet Adam AS, while shaitan was reluctant to kowtow because he felt better because he was created from fire while man was created from a clod of earth. The pride of the shaitan caused Allah to impose the punishment that the shaitan took out of heaven. However, shaitan pleaded for the punishment to be suspended by vowing he would tempt people until the end of time. Therefore, shaitan both in the form of jinn and man always tempts to do things that Allah Almighty forbids.